Spatiotemporal variations in channel changes caused by cumulative factors in a meandering river: The lower Peixe River, Brazil - Morais, Eduardo S. [UNESP] (2016)
Channel changes in meandering rivers naturally exhibit complex behaviour, and understanding the river dynamics can be challenging in environments also subject to cumulative human impacts. Planform changes were analysed on four reaches of the lower course of the Peixe River, Brazil, at decadal scales over the period 1962-2008 from aerial photographs and satellite imagery, complemented by a historical map from 1907. Analysis of the spatial and temporal patterns of channel change mechanisms and morphometry of bends and of the sinuosity and morphodynamic variations of the reaches demonstrates major changes in planform characteristics. Sinuosity in all reaches decreased from similar to 2.6 to similar to 1.7, average wavelength of bends has increased from similar to 200 to similar to 500 m, and the planform has become much simpler. Changes have been progressive from downstream to upstream, with higher intensities of processes, particularly cutoffs first in downstream reaches then more recently in upstream reaches. It is suggested that channel changes represent a morphological adjustment to human interventions, such as reservoir construction and land use. However, evidence of the autogenic behaviour of meanders is highlighted in which the existence of compound meanders reveals control over the spatial variation in the reaches. The results suggest that geomorphic thresholds associated with the compound meander formation and the bend evolution should be considered, even in impacted meandering rivers, because they exert primary controls on the spatial-temporal adjustment of channels. (C) 2016 Elsevier B.V. All rights reserved.